Advocating for children and families in an emerging democracy : the post-Soviet experience in Lithuania - Kugelmass, Judy W.; Ritchie, Dennis J. (Research in global child advocacy., 2003)
This book investigates issues surrounding the creation of social policy and support systems for children and families in this emerging democracy. Approaches advocated by progressively oriented Lithuanian educators, mental health and human service professionals toward addressing these conditions are presented by Lithuanian and American educators and mental health practitioners who have been working toward the development of democratically based social institutions.